Considerations in The Design of Longwall Mining Systems - Thomas M. Barczak; Claude A. Goode (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Principal criteria in the design and operation of longwall mining systems are examined. The decision to apply longwall mining is investigated from an economic viewpoint, and the impact of economics on system design are addressed. Geological considerations and requirements for effective long- wall mining are provided. Ground control factors determining panel design are outlined, as well as environmental considerations. Operational practices are discussed and alternatives recommended. The impact of face moves and the potential for mining wider webs are assessed. Constraints to production are identified and the potential for increasing production of longwall systems is established.